Advancing full production and increasing yield in young 'Triumph' persimmon orchards - Scheepers, Stephanus Jacobus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Horticulture))--University of Stellenbosch, 2010.